Molecular Targets and Emerging Therapeutic Options for Uterine Leiomyosarcoma. (19th September 2016) - Miller, Heather; Ike, Chiemeka; Parma, Jennifer; Masand, Ramya P.; Mach, Claire M.; Anderson, Matthew L.
Abstract : Uterine leiomyosarcoma (uLMS) is an aggressive malignancy characterized by its early metastasis, high rates of recurrence, and poor prognosis. Multiple obstacles complicate the clinical management of uLMS. These include the fact that most uLMS are typically identified only after a woman has undergone hysterectomy or myomectomy, the limited efficacy of adjuvant therapy for early stage disease, and the poor response of metastatic disease to current treatments. Here, we discuss recent insights into the molecular basis of uLMS and discuss emerging options for its clinical management. Particular attention is given to the biologic basis of these strategies with the goal of understanding the rationale motivating their use.